1998
DOI: 10.2134/agronj1998.00021962009000030004x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Treatments for Delaying Senescence of Wheat Leaves: II. Senescence and Grain Yield under Field Conditions

Abstract: Longevity of leaves directly influences grain yield of wheat (Triticum aestivum L.), but is greatly diminished by environmental stresses. The objective of these studies was to identify treatments that might delay senescence of wheat leaves and increase grain yield. ‘Nesma’ wheat was grown on a heavy clay soil at Meknes, Morocco, for two seasons, the first characterized by mild stress and the second by more severe stress from inadequate precipitation and high temperature. Three planting dates, two seeding rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 27 publications
3
41
1
1
Order By: Relevance
“…While the number of fertile tillers and grains has been determined before anthesis (Elliott et al 1997), it appears that in some instances an application of P after anthesis does have the capacity to increase yield through increased grain fill. Benbella and Paulsen (1998) found that applications of P to wheat after anthesis increased yield while Gray (1977) reviewed several experiments that showed yield responses to foliar P applications after anthesis.…”
Section: Timing Of In-season P Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the number of fertile tillers and grains has been determined before anthesis (Elliott et al 1997), it appears that in some instances an application of P after anthesis does have the capacity to increase yield through increased grain fill. Benbella and Paulsen (1998) found that applications of P to wheat after anthesis increased yield while Gray (1977) reviewed several experiments that showed yield responses to foliar P applications after anthesis.…”
Section: Timing Of In-season P Applicationsmentioning
confidence: 99%
“…Based on our review of the literature the most appropriate timing for application is at early pod development in soybeans (Gray 1977), from canopy closure to anthesis in cereal crops (Benbella and Paulsen 1998;Mosali et al 2006;Girma et al 2007) and early tasseling in maize/corn (Harder et al 1982;Giskin and Efron 1986;Girma et al 2007). The rate of application is dependent on crop requirement, crop type, number of applications, water volume and salt loading but in general 1.5-4 kg P ha -1 gave the best results (Benbella and Paulsen 1998; Mosali et al 2006;Girma et al 2007).…”
Section: Foliar Phosphorus Fertilisation Of Dryland Cropsmentioning
confidence: 99%
“…This period is known as the lag phase, during which cellular division is rapid and endosperm cells and amyloplasts are formed, and is considered very sensitive to environmental stresses [125].…”
Section: Plant Treatmentsmentioning
confidence: 99%
“…This trade-off is under environmental control but also depends on the genotype, as illustrated by the stay-green behaviour of some crop cultivars. These are characterized by their ability to maintain significant areas of vegetative tissues that are still photosynthetic at maturity (Benbella and Paulsen, 1998;Borrell et al, 2001), but the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%